Analisis Pemahaman dan Kepatuhan Pelaku UMKM tentang Pajak Daerah di Kabupaten Pamekasan - Triananda Novi Safitri; Lukmanul Hakim (Jurnal Ragam Pengabdian, 2026)
This research seeks to examine the degree to which Micro, Small, and Medium Enterprises (MSMEs) in Pamekasan Regency comprehend and adhere to local tax obligations following the implementation of Law Number 1 of 2022 concerning Fiscal Relations between the Central and Regional Governments. A descriptive qualitative approach was adopted, with data gathered through in-depth interviews and direct observation of MSME operators within the food and beverage industry. The results reveal that MSME operators' grasp of local taxation remains at a relatively low to moderate level, particularly with respect to tax categories, functions, procedures, and the consequences of non-compliance. Levels of tax payment adherence were found to differ considerably among business operators; whereas certain individuals fulfill their obligations consistently and punctually, others tend to make payments only after receiving reminders from relevant authorities. The principal causes behind non- compliance encompass inadequate dissemination and public education on the part of the government, coupled with insufficient supervision and law enforcement mechanisms. These results highlight the pressing necessity for more robust socialization programs, strengthened educational outreach, and the development of a more effective monitoring framework to elevate tax awareness and compliance among MSME operators. Such advancements are indispensable not merely for cultivating a culture of voluntary tax fulfillment, but also for maximizing regional revenue generation, thereby advancing sustainable local development and the delivery of public services in Pamekasan Regency.